2021
DOI: 10.1002/adfm.202105264
|View full text |Cite
|
Sign up to set email alerts
|

Muscle‐Inspired MXene Conductive Hydrogels with Anisotropy and Low‐Temperature Tolerance for Wearable Flexible Sensors and Arrays

Abstract: Conductive hydrogels as flexible electronic devices, not only have unique attractions but also meet the basic need of mechanical flexibility and intelligent sensing. How to endow anisotropy and a wide application temperature range for traditional homogeneous conductive hydrogels and flexible sensors is still a challenge. Herein, a directional freezing method is used to prepare anisotropic MXene conductive hydrogels that are inspired by ordered structures of muscles. Due to the anisotropy of MXene conductive hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
186
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 249 publications
(188 citation statements)
references
References 51 publications
2
186
0
Order By: Relevance
“…Although the conductivity of hydrogels is lower than that of metal electrodes, the internal resistance is still acceptable. For example, when connecting the PVA/MXene hydrogel prepared by Feng et al [53] into a closed circuit, the green LED could be lit up (Figure 3g). Notably, it is found that the internal resistance of many H-TENGs is lower than that of common metal electrode-based TENGs, which may benefit the power circuit management and powering/charging of portable/wearable electronics.…”
Section: Reduced Internal Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Although the conductivity of hydrogels is lower than that of metal electrodes, the internal resistance is still acceptable. For example, when connecting the PVA/MXene hydrogel prepared by Feng et al [53] into a closed circuit, the green LED could be lit up (Figure 3g). Notably, it is found that the internal resistance of many H-TENGs is lower than that of common metal electrode-based TENGs, which may benefit the power circuit management and powering/charging of portable/wearable electronics.…”
Section: Reduced Internal Resistancementioning
confidence: 99%
“…Reproduced with permission. [ 53 ] Copyright 2021, Wiley‐VCH. h) Output power of the TENG/Ecoflex device versus resistive load.…”
Section: Advantages Of Hydrogels As Ionic Conductors In Tengsmentioning
confidence: 99%
“…A significant increase in electrical conductivity is attributable to favorably connected Ti 3 C 2 T x nanosheets for an extraordinary electron transport ability [ 37 , 38 ]. Notably, compared to other conductive hydrogels reported previously [ 39 ], our Ti 3 C 2 T x -PAA hydrogel exhibits superior conductivity to most hydrogels so far (see detailed comparison in Table S2 [ 36 , 40 , 41 , 42 , 43 ]). Highly conductive Ti 3 C 2 T x -PAA hydrogel may also be utilized for potential applications in flexible and wearable electronic devices [ 3 , 44 ].…”
Section: Resultsmentioning
confidence: 66%
“…; Table S1: Compositions of Ti 3 C 2 T x -PAA hydrogels, Table S2: Electrical conductivity comparison of our Ti 3 C 2 T x -PAA hydrogels with previously reported conductive hydrogels. References [ 36 , 40 , 41 , 42 , 43 ] are cited in Supplementary Materials.…”
mentioning
confidence: 99%
“…[11][12][13][14][15] Depending on the structure design, different deformations of the conductive component, which are stretching, compression, bending and twisting, have been realized. [5][6][7][16][17][18] However, it remains challenging to achieve all these deformations in a single structure design.Among the structural designs, porous structure has the capability to detect tensile, compressive, and torsional strains. [5][6][7]10] Due to the high porosity, porous structures can be largely compressed that they have been widely used to detect compressions.…”
mentioning
confidence: 99%